2021
DOI: 10.3390/foods10112631
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplex PCR Assay Combined with Capillary Electrophoresis for the Simultaneous Identification of Atlantic Cod, Pacific Cod, Blue Whiting, Haddock, and Alaska Pollock

Abstract: With an increased consumption of seafood products, food fraud with fish resources has been continuously reported. In particular, codfish has been exploited worldwide as a processed product in fresh, frozen, smoked, canned, or ready-to-eat dish forms. However, it is challenging to identify processed fish products after processing because of their similar morphological characteristics. Substitution and mislabeling of codfish among different species are also happening deliberately or unintentionally. Thus, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
(44 reference statements)
0
8
1
Order By: Relevance
“…Compared to previous study [35], the primers developed in this study could detect bigeye, skipjack, albacore, and yellowfin tunas' DNA even in low concentrations. Conventional PCR has been reported to be less specific and sensitive than real-time PCR [35,36]. However, the assay conducted in this study based on conventional PCR had higher detection sensitivity than reported by previous studies.…”
Section: Specificity and Sensitivity Of Single Pcrcontrasting
confidence: 60%
See 2 more Smart Citations
“…Compared to previous study [35], the primers developed in this study could detect bigeye, skipjack, albacore, and yellowfin tunas' DNA even in low concentrations. Conventional PCR has been reported to be less specific and sensitive than real-time PCR [35,36]. However, the assay conducted in this study based on conventional PCR had higher detection sensitivity than reported by previous studies.…”
Section: Specificity and Sensitivity Of Single Pcrcontrasting
confidence: 60%
“…Capillary electrophoresis has been reported to provide higher resolution than agarose-based electrophoresis when distinguishing DNA amplicons [36]. Then, the multiplex PCR method coupled with capillary electrophoresis was conducted to detect the five species of tunas [36]. The sensitivity of the developed multiplex PCR detected by capillary and agarose-based electrophoreses was 1 pg (Figures 4 and 5).…”
Section: Specificity and Sensitivity Of Multiplex Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…The putative candidate genes identified in this work could be useful for enhancing the shelf life of dessert-type cantaloupe melons. CE methodologies applied to DNA analysis reported in the last 2 years have been aimed at assessing food safety [57][58][59], detecting genetically modified organisms (GMOs) [60,61], evaluating food authenticity [62,63], and detecting food fraud [64,65].…”
Section: Dnasmentioning
confidence: 99%
“…PCR-based techniques, such as DNA barcoding, PCR restriction fragment length polymorphism, forensically informative nucleotide sequencing, and recombinase polymerase amplification, have been developed to detect different species [ 11 , 12 , 13 , 14 ]. These techniques have been used to identify commercially important seafood species, such as shrimps, cods, crabs, and oysters [ 8 , 15 , 16 , 17 ]. Recently, more rapid and convenient technologies have been developed to confirm the presence of target species in processed foods [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%